Peran Konseling Individu dalam Membantu Mengatasi Masalah Korban Trauma Kecelakaan Lalu Lintas - Nyolanda Wulandari Koto; Ainul Mardiyah; Mutiara Permata Hati Br. Sinaga; Fahmi Irawan (Lembaga Pengembangan Kinerja Dosen, 2026)
This study employed a descriptive qualitative approach using a case study design to explore the psychological impacts of traffic accidents on victims. Data were collected through semi-structured interviews and direct observation, then analyzed using thematic analysis techniques. The findings indicate that the main trauma-related symptoms include intense negative thoughts or emotions, such as sudden fear, nausea, and mood changes characterized by increased sadness and irritability. Additionally, sleep disturbances were observed, including vivid nightmares, flashbacks when attempting to sleep, and physical reactions such as heart palpitations. Avoidance behaviors were also noted, such as avoiding the accident location, rarely leaving the house, and avoiding conversations related to the accident. Traffic accidents are sudden, unexpected events that can cause not only physical injuries but also profound psychological impacts, including fear, excessive anxiety, nightmares, and symptoms of post-traumatic stress disorder (PTSD). If left untreated, these psychological disorders may interfere with daily functioning and significantly reduce the quality of life of the victims, making early intervention crucial for recovery.